Prépositions et langage chez de jeunes sourds profonds oralistes - Laurence Vincent-Durroux (Corela)
Prelingual profound deafness may have consequences on the representation of space and time, consequences which may appear in the deaf’s linguistic productions. This paper presents the analysis of the use of prepositions in oral data gathered from oral deaf subjects who speak either French or English ; the analysis aims at hypotheses on specificities in the language of the profoundly deaf. Problematic utterances are related to superfluous, inadequate or missing prepositions. In the first two cases, there are problems in syntactic linearity. As concerns missing prepositions, phonological and cognitive hypotheses can be considered, in relation to space, time, categorisation, and the description of prepositions in Belgian Sign Language. The results are discussed in terms of predication, of the specificity of the French preposition "pour", and the possible role of visual representation of the relationships between referents.